(3GdYbO GdKejf aj JGQjN GdHdO GdCejfs - (3Jbi GdOjf eMeO Hf eMeO Hf CMeO Hf Ydj GdMSfj GdaGSi Gdecj,J (B832 (3g` s ((3aNQ GdOjf CHh HcQ Hf eMeO Hf eSYhO Hf PhGO GdGaYi GdYRGFi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChSY def TGA ef Ndbg ai GdQRb hGdCLd CeG HYO aEfi deG habfi Gdgd JYGdi ddETJZGd HGdYde JThbJ faSi cKjQkG Edi eYQaI JQGLe GdCYjGf ef Cgd ecI s
(3BNQgG (B:s
(3hBNQg HYO ef CSeg eMeO ZjQ efShH (B:(3W Je GdLRA GdChd ef cJGH GdYbO GdKejf s
(3cJHJ GdYfGhjjf hCSeGA GdeJQLejf HGdMeQIs
(3hai UOQ GdfSNI JedcGJ ZjQ eDQNgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
Keywords: (3GdJGQjNs